(untitled) (Journal of the College of Basic Education, 2022)
The study deals with the actual structure of the compositions in Surat Al-Shams Al-Blessed, by looking at the chain of transmission in the actual composition, its requirements, its complement, and other related elements. To demonstrate the semantic result of these compositions in the context of the particular verse and then the general context of the surah, by analyzing the structure of the compositions that connect to verbs, and stating the deletion, introduction and delay, and the interrelation of these elements with each other, and their effect on the attachment of the structures to each other, the surah is full of actual combinations It influenced its general construction and enriched its connotation; As one of its fifteen verses is not devoid of action, outwardly or appreciating, and this is a hoarder and an indication that comes from the main role of verbs in building structures, and their effect on other elements of the composition both in action and in significance. The verb is the pole of the verbal sentence, and it is related to the construction of its composition, the arrangement of its elements, and the production of its meaning.